Palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia as well as synthesis method and application of palladium-cobalt nano-microsphere material
By developing PdxCoy, a palladium-cobalt nano-microsphere material, and adjusting its chemical composition and morphology, the insufficient performance problems of Co3O4 electrocatalyst in the electrocatalytic nitrate reduction process were solved, and efficient and stable ammonia synthesis effect was achieved.
Patent Information
- Application Number
- CN202411838007.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-22
AI Technical Summary
The existing Co3O4 electrocatalysts have problems such as large band gap, low conductivity, poor adsorption characteristics to NO3- and unsatisfactory selectivity to NH3 during the electrocatalytic nitrate reduction process, which limits their application in ammonia synthesis.
A palladium-cobalt nano-microsphere material PdxCoy was developed to improve the electronic structure and activity of the catalyst by adjusting the molar fraction of Pd and Co and the morphology of the nano-microspheres, thereby achieving efficient ammonia synthesis.
The Pd0.5Co0.5 catalyst showed the highest NH3 yield and Faraday efficiency at -1.0V vs.RHE, with NH3 selectivity up to 96.8±0.9%, and maintained stability and activity over long and multiple cycle tests.
Smart Images

Figure CN119859820A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to electrocatalytic synthesis of ammonia, in particular to a palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia and a synthesis method and application thereof. Background Art
[0002] Ammonia (NH3) is the most widely used chemical in production and life, with an annual output of more than 200 million tons. It not only plays a very important role in the manufacture of agricultural fertilizers and industrial products, but also has a high energy density (4.3kWh kg -1 ) and is pollution-free and is regarded as the next generation energy carrier.
[0003] The traditional method of producing NH3 is through the Haber-Bosch process, in which H2 and N2 are mixed and reacted at high pressure (200-300atm) and high temperature (450-500℃) to produce NH3. However, this method has many challenges. First, high-purity H2 needs to be prepared, which is usually achieved through an energy-intensive steam reforming process. On average, 7.5-12 tons of CO2 are emitted for every ton of H2 produced, which has a high carbon footprint. To overcome these challenges, people have begun to explore alternative strategies, such as converting nitrates into NH3 and other value-added products through electrochemical reduction. This electrocatalytic nitrate reduction process can be carried out under ambient conditions, and the N=O dissociation energy is low at 204kJ mol -1 In the past few years, a series of materials have been used as NRA electrocatalysts. Among them, Co-based electrocatalysts have attracted wide attention due to their low cost and excellent NRA performance. Some studies have reported the performance of Co-based electrocatalysts, especially Co3O4, in NO3 - However, due to the large band gap and low conductivity, the conversion of NO3 - The poor adsorption characteristics and unsatisfactory selectivity for NH3 limit their further applications. In order to improve the intrinsic activity of Co3O4 in NRA, a lot of work has been done, such as defect engineering, surface modification and heteroatom doping. Summary of the invention
[0004] The first purpose of the present invention is to develop a palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia with high catalytic efficiency and easy output and a synthesis method thereof;
[0005] The second object of the present invention is to provide an application of palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia, which has a stable system, high efficiency and can be realized at room temperature.
[0006] To achieve the above-mentioned purpose of the present invention, the present invention discloses a palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia, wherein the material morphology of the nano-microsphere is spherical; its chemical composition is characterized by Pd x Co y , x and y represent the molar fractions of Pd and Co respectively, x+y=1, and the ratio of x to y ranges from 15:85 to 50:50; and the diameter of the nanospheres is 100 to 300 nm.
[0007] Furthermore, when the material is used as an electrocatalyst to catalyze the synthesis of ammonia, when the ratio of x to y is 1, that is, when x = y = 0.5, the loading amount is 0.4 mg cm -2 When Pd 0.5 Co 0.5 The catalyst has the highest NH3 yield of 1.72±0.03mg h at -1.0 V vs. RHE. -1 mg cat -1 and Faradaic efficiency 88.9±1.2%; when the initial concentration of nitrate is 100ppm, the NH3 selectivity is as high as 96.8±0.9%.
[0008] Furthermore, at this time, the diameter of the nano-microspheres is about 300 nm and is evenly distributed.
[0009] Furthermore, after five cycle tests, it showed good stability and activity; after a long-term test of 48 hours, its current density remained basically stable, with good durability.
[0010] The above-mentioned method for synthesizing the palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia is as follows:
[0011] A quantitative amount of 19.2 mg to 101.1 mg PdCl2 and 146.5 mg to 26 mg CoCl2 was dissolved in 30 mL methanol solution. Under continuous stirring, 8 mL ZIF-67 suspension was transferred to the mixed solution. After being in a water bath at 50 to 70 ° C for 2 h to 3 h, the mixture was washed three times with methanol. After drying overnight, the obtained powder sample was annealed at 360 ° C for 2 h to 3 h in an Ar atmosphere to obtain Pd x Co y ; Pd was adjusted by changing the amount of PdCl2 and CoCl2 x Co y The molar fractions of Pd and Co in x Co y The x and y in the equation represent their respective mole fractions.
[0012] The application of the above-mentioned palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia is applied to electrocatalytic nitrate reduction synthesis of ammonia.
[0013] Furthermore, the material is prepared into a working electrode for electrocatalytic reduction of synthetic ammonia, specifically in the following steps:
[0014] Electrolyte configuration: The electrolyte concentration used is 100ppm NO3 - -N+0.1M Na2SO4 solution;
[0015] Nafion 115 membrane treatment: The Nafion 115 membrane cut to the appropriate size was soaked in 80℃ 5wt% hydrogen peroxide for 1 hour, transferred to deionized water for 30 minutes, then treated in 80℃ 5wt% dilute sulfuric acid for 1 hour, and finally transferred to 80℃ deionized water for 30 minutes;
[0016] Preparation of working electrode: Prepare the above-prepared Pd x Co y The catalyst was added to a mixed solution of ethanol and Nafion solution, wherein the volume ratio of ethanol to Nafion was 19:1; ultrasonic treatment was performed for 20 to 40 minutes to form a uniform suspension, and 200 μL of the suspension was evenly dropped on carbon paper (1.0 cm×1.0 cm), and vacuum dried for later use;
[0017] Electrocatalytic NO3 - Reduction test: The electrochemical experiment was carried out in an H-type electrolytic cell separated by a Nafion 115 membrane, using a three-electrode system to load Pd x Co y The carbon paper of the catalyst was used as the working electrode, the platinum mesh electrode was used as the counter electrode, and the Ag / AgCl electrode (filled with saturated KCl solution) was used as the reference electrode to form a three-electrode system; the test environment was room temperature and atmospheric pressure;
[0018] Before the test begins, Ar needs to be passed through the electrolyte for 20 minutes in advance to remove O2 in the electrolyte, and Ar should be kept flowing steadily in subsequent tests; the stirring rate during the test is 200-250rpm; the LSV test scan rate is 5mV / s, and it is carried out in the potential range of 0Vvs.RHE to -1.1Vvs.RHE; the constant potential test lasts for 1-1.5h at a potential of -1.1 to -0.7Vvs.RHE.
[0019] Furthermore, all potentials of the system are converted into reversible hydrogen electrode potentials by the following formula:
[0020] E(vs.RHE)=E(vs.Ag / AgCl)+0.059pH+0.197
[0021] The synergistic effect between Pd and Co in this patent improves the electronic structure of the catalyst, making Pdx Co y It showed remarkable selectivity and high efficiency. 0.5 Co 0.5 The adaptability and long-term cycle stability in nitrate solutions of different concentrations are excellent. This achievement provides a new catalytic material idea for the electroreduction of nitrates to synthesize ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The detailed description given as non-limiting examples better explains what the invention consists of and how it can be implemented, and furthermore, refers to the accompanying drawings, in which:
[0023] Figure 1 SEM images of (a) Co (b) Pd0.15Co0.85 (c) Pd0.85Co0.15 (d) Pd;
[0024] Figure 2 For the preparation of different proportions of Pd x Co y XRD;
[0025] Figure 3 For different proportions of Pd x Co y XPS spectra of (a) Pd 3d; (b) Co 2p;
[0026] Figure 4 (a) TEM image of Pd0.15Co0.85, (bc) mapping image, (d) HRTEM image; (e) Pd 0.5 Co 0.5 TEM image, (fg) mapping image, (h) HRTEM image; (i) TEM image, (jk) mapping image, (l) HRTEM image of Pd0.85Co0.15;
[0027] Figure 5 (a) Pd x Co y LSV diagram of catalyst in 0.1M Na2SO44 electrolyte with and without NaNO3 (b) Pd with different ratios x Co y Yield and FE at -1.0 V vs. RHE; (c) Yield and FE at different potentials (d) Pd 0.5 Co 0.5 Product selectivity of the catalyst at different nitrate concentrations (e) 15 NO3 - and 14 NO3 -1H NMR spectra of nitrate electrolytes used as N sources after electrolysis; (f) Detection of NH3 yield by different quantitative methods;
[0028] Figure 6 (a) Pd 0.5 Co 0.5 IT curves of 1 h reaction at different potentials; (b) corresponding UV-visible absorption spectra;
[0029] Figure 7 For different loading amounts of Pd 0.5 Co 0.5 NRA electrochemical performance of the catalyst. (a) UV-visible absorption spectrum after 1 h of reaction; (b) NH3 yield and FE;
[0030] Figure 8 (ae) Pd with different ratios x Co y CV diagrams of the catalysts, Co and Pd 0.5 Co 0.5 , Pd 0.15 Co 0.85 , Pd 0.85 Co 0.15 , Pd; (f) Pd with different ratios x Co y Double layer capacitance;
[0031] Fig. 9 Stability test (a) Stable NH3 yield and FE after five cycles; (b) long-term IT curve. DETAILED DESCRIPTION
[0032] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] Preparation of ZIF-67
[0034] Co(NO3)2·6H2O (0.3 g) and 2-methylimidazole (1.2992 g) were added to 100 mL of methanol solution, and the 2-methylimidazole solution was poured into the cobalt nitrate solution, stirred continuously for 30 min, allowed to stand for 24 h, and centrifuged to obtain dodecahedral ZIF-67, which was washed three times with methanol. Finally, ZIF-67 powder was dispersed in methanol to prepare ZIF-67 suspension.
[0035] Preparation of ZIF-8
[0036] The method is the same as ZIF-67, but Zn(NO3)2·6H2O is used instead of Co(NO3)2·6H2O.
[0037] Pd x Coy Preparation and characterization of electrocatalysts
[0038] Pd x Co y The synthesis method of Figure 1 As shown in a, a certain amount of PdCl2 and CoCl2 were dissolved in 30 mL of methanol solution, and the ZIF-67 suspension (0.8 mL) was transferred to the mixed solution under continuous stirring. After being in a water bath at 60 ° C for 2 h, it was washed three times with methanol. After drying overnight, the powder sample was annealed at 360 ° C in an Ar atmosphere for 2 h to obtain Pd x Co y The amount of PdCl2 and CoCl2 was varied to adjust the x Co y The molar fractions of Pd and Co in x Co y The x and y in the equation represent their mole fractions.
[0039] Figure 1 Figure a is the SEM image of the Co sample, which has a relatively uniformly dispersed block structure. With the addition of metal Pd, the crystal structure aggregates. Figure 1 bPd 0.15 Co 0.85 The morphology gradually grows into a spherical structure with uneven size. Figure 1 c shows that when the ratio is Pd 0.5 Co 0.5 When the ratio is Pd 0.85 Co 0.15 When the spherical structure collapses, it becomes irregular particles ( Figure 1 c), Figure 1 The d shows that the pure Pd sample is irregular blocky, which shows that Pd doping may cause the crystal structure to rearrange and recombine, resulting in changes in the shape and size of the grains.
[0040] Figure 2 For different proportions of Pd x Co y The XRD spectrum of the bimetallic material shows that the diffraction peak gradually shifts to the left as the content of metal Pd increases. 0.5 Co 0.5 When the ratio is Pd, the diffraction peak is located at 39.68°, which is between the (311) crystal plane of Co3O4 and the (111) crystal plane of Pd, close to the (111) crystal plane of Pd, and the diffraction peak intensity is weak. 0.85 Co 0.15The intensity of the diffraction peak increases when the Pd content increases. As the Pd content increases, the diffraction peak originally attributed to Co3O4 gradually shifts. This shift is due to the insertion of Pd atoms into the crystal structure, resulting in lattice expansion and peak displacement. The atomic radius of Pd atoms is larger than that of Co, so strain is introduced into the lattice, thereby changing the original Co3O4 phase. This transition reflects the gradual dominance of Pd in the crystal structure, causing the material to transition from a cobalt oxide phase to a Pd-Co mixed state.
[0041] The morphology and structure of the samples were characterized by X-ray diffractometer (Ultima IV, Rigaku Corporation, Japan), scanning electron microscope (GeminiSEM300, Zeiss, Germany), transmission electron microscope (TecnaiG2F30, FEI, USA), and X-ray photoelectron spectroscopy (ESCALAB250Xi, Thermo Fisher Scientific, USA).
[0042] Electrochemical measurements
[0043] Electrolyte configuration: The electrolyte concentration used is 100ppm NO3 - -N+0.1M Na2SO4 solution (30mL), wherein the nitrate is NaNO3.
[0044] Nafion 115 membrane treatment: The Nafion 115 membrane cut to a suitable size was soaked in 80°C 5wt% hydrogen peroxide for 1 hour, transferred to deionized water for 30 minutes, then treated in 80°C 5wt% dilute sulfuric acid for 1 hour, and finally transferred to 80°C deionized water for 30 minutes.
[0045] Working electrode preparation: 2 mg of prepared Pd x Co y The catalyst was added to a mixed solution of 950 μL ethanol and 50 μL Nafion solution, and ultrasonicated for 20 min to form a uniform suspension. 200 μL of the suspension was evenly dropped on carbon paper (1.0 cm×1.0 cm), and then vacuum dried for later use.
[0046] Electrocatalytic NO3 - Reduction test: The electrochemical experiments were carried out in an H-type electrolytic cell separated by a Nafion 115 membrane, using a three-electrode system to load Pd x Co y The carbon paper of the catalyst was used as the working electrode, the platinum mesh electrode was used as the counter electrode, and the Ag / AgCl electrode (filled with saturated KCl solution) was used as the reference electrode. All potentials in this system were converted into reversible hydrogen electrode potentials using the following formula.
[0047] E(vs.RHE)=E(vs.Ag / AgCl)+0.059pH+0.197
[0048] NO3 - The reduction reaction was carried out at room temperature and atmospheric pressure, and the electrochemical test was performed using a DH7000 electrochemical workstation. Before the test began, Ar was introduced into the cathode electrolyte for 20 min in advance to remove O2 from the electrolyte, and Ar was kept steadily introduced in subsequent tests. The electrolyte stirring rate was 200 rpm. The LSV test scan rate was 5 mV / s, and it was carried out in the potential range of 0 V vs. RHE to -1.1 V vs. RHE. The constant potential test lasted for 1 h at potentials of -0.7, -0.8, -0.9, -1.0 and -1.1 V vs. RHE, respectively. Pd x Co y Electrocatalytic nitrate reduction performance test
[0049] First, LSV tests were performed in Ar-saturated 0.1M Na2SO4 electrolyte with and without NaNO3 added to the electrolyte to study the x Co y The NRA catalytic activity.
[0050] like Figure 5 As shown in a, the current density increased significantly when NaNO3 was added, which indicated that Pd x Co y It has high activity against NRA.
[0051] We quantified the Pd x Co y First, the different ratios of Pd x Co y The catalyst was subjected to a constant potential test at -1.0 V vs. RHE for 1 h.
[0052] Depend on Figure 5 b It can be seen that Pd 0.5 Co 0.5 The catalytic performance of Pd 0.5 Co 0.5The catalyst exhibits the best catalytic performance at -1.0Vvs.RHE, which is mainly attributed to the catalytic synergistic effect between palladium (Pd) and cobalt (Co). As a transition metal, Pd has a high hydrogen adsorption capacity, which can effectively promote the reduction of NO3- and help the rapid conversion of intermediates. Co shows good activity in the reduction of nitrogen oxides, which helps to reduce the formation of by-products and improve the reaction selectivity. After the two are alloyed in a suitable proportion, the electronic structure of Pd is optimized due to the presence of Co, which weakens its interaction with the reaction intermediates, thereby reducing the activation energy of the reaction. In addition, the surface geometry of the alloy increases the utilization of active sites and stabilizes some key intermediates. This synergistic effect greatly increases the reduction reaction rate, ultimately making Pd 0.5 Co 0.5 The ammonia yield and Faraday efficiency of the catalyst were better than those of other catalysts. Therefore, Pd 0.5 Co 0.5 Catalyst. According to the LSV results, a constant potential test was carried out for 1 h in the potential range of -0.7 V vs. RHE to -1.1 V vs. RHE, and the product NH3 was determined after electrolysis.
[0053] During the 1h constant potential test, the more negative the potential, the greater the current density, and the current density is in a relatively stable state ( Figure 6 a curve), indicating that Pd 0.5 Co 0.5 It has good stability. The UV-visible absorption spectrum after 1h of reaction ( Figure 6 b), the absorbance continues to increase. At the same time, we found that the Faraday efficiency (FE) showed a trend of first increasing and then decreasing; Figure 5 As shown in Figure c, at -1.0 V vs. RHE, FE reaches its maximum value, and then FE decreases, which may be due to the competitive hydrogen evolution reaction. Therefore, we choose -1.0 V vs. RHE as the optimal potential, and the ammonia yield at this time is 1.72 ± 0.03 mgh -1 mg cat -1 , FE is 88.9±1.2%, indicating that Pd 0.5 Co 0.5 The catalyst has high activity towards NRA.
[0054] Product selectivity is an important evaluation index of NRA performance, so we explored the effect of different initial nitrate concentrations on product selectivity. Figure 5 d is the selectivity of NH3 and NO2 when the initial concentration of nitrate is 50ppm, 100ppm and 200ppm -Selectivity: The selectivity of NH3 is always higher than 90%, with a wide range of concentration adaptability. When the initial concentration of nitrate is 100ppm, the selectivity is the best, among which the selectivity of NH3 is 96.8±0.9%, and the selectivity of NO2 is - Selectivity: 2.1 ± 0.5%.
[0055] In addition, we 0.5 Co 0.5 The catalyst loading on carbon paper was also optimized. Figure 7 a is different load Pd 0.5 Co 0.5 The UV-visible absorption spectrum of the product ammonia after 1 h of electrocatalysis shows that different loading amounts of the catalyst have different electrocatalytic properties. Figure 7 b shows that the NH3 yield and FE increase first and then decrease with the increase of the loading amount. When the loading amount is 0.4 mg cm -2 The performance decreased after reaching the maximum value, which may be due to the increase in loading amount leading to catalyst agglomeration or the increase in the thickness of the catalyst layer, which restricted the mass transfer and limited the diffusion of the reactants to the vicinity of the active sites, thus reducing the reaction rate. Therefore, 0.4 mg cm -2 For the optimal load.
[0056] NH3 detection
[0057] The NH3 produced in the cathode electrolytic cell was determined by the indophenol blue method.
[0058] The developer A was prepared as 1 M NaOH (containing 5 wt % sodium salicylate and 5 wt % trisodium citrate), the developer B was prepared as 0.05 M NaClO, and the developer C was prepared as 1 wt % sodium nitrosoferrocyanide solution.
[0059] Dry ammonium chloride at 105℃ for 2h, cool to room temperature, weigh 0.3821g, dissolve in 0.1M Na2SO4, prepare 1000μg / mL NH3 standard stock solution, take 1mL 1000μg / mL NH3 standard stock solution, dilute with 0.1M Na2SO4 solution to 10μg / mL NH3 standard stock solution. Then take 0, 2, 4, 6, 8 and 10mL of 10μg / mL NH3 standard stock solution in turn to prepare 0μg / mL, 0.4μg / mL, 0.6μg / mL, 0.8μg / mL, 1.0μg / mL and 2.0μg / mL NH3 standard solutions, take 4mL NH3 standard solution, and add 500μL color developer A, 50μL color developer B, and 50μL color developer C solution. After color development in a dark environment for 1 h, the absorbance was measured using a UV-visible spectrophotometer and a standard curve was drawn.
[0060] XPS was used to determine the elemental composition and valence state analysis of the materials. Figure 3 For different proportions of Pd x Co y XPS spectra of (a) Pd3d, (b) Co 2p; High-resolution XPS spectra of Pd 3d ( Figure 3 a), can be attributed to Pd 0 For the high-resolution XPS spectra of Co 2p ( Figure 3 b), the peaks at 779.83 eV and 794.85 eV are attributed to Co 3+ 2p 1 / 2 and Co 3+ 2p 3 / 2 The peaks at 781.41 eV and 796.44 eV are attributed to Co 2+ 2p 1 / 2 and Co 2+ 2p 3 / 2 , the peaks at 789.6eV and 804.5eV are satellite peaks.
[0061] With the increase of Pd content x Co y The binding energy of Co in Pd is negatively shifted compared to pure Co. x Co y 3D Pd 5 / 2 The binding energy of Pd is positively shifted compared with pure Pd, which means that after adding Pd, some electrons are transferred from Pd atoms to Co. The electronic interaction between Pd and Co changes the electronic state of the catalytic reaction site, thereby improving its catalytic activity.
[0062] The surface morphology of the sample was further observed by transmission electron microscopy (TEM), and the crystal plane index of the sample was determined based on the lattice fringe spacing of high-resolution transmission electron microscopy (HRTEM) and XRD. Figure 4 a further revealed that Pd 0.15 Co 0.85 The spherical structure, Figure 4 The bc mapping diagram shows that Pd is coated with Co. Figure 4 The clear lattice fringes in the HRTEM image (d) show the (311) plane of Co3O4, which is consistent with the results of the XRD spectrum.
[0063] Pd 0.5 Co 0.5 TEM images of Figure 4 e) The spherical outline is clearly shown, Figure 4 Pd and Co in the fg mapping diagram are evenly distributed. Figure 4The spacing of the lattice fringes in the HRTEM image of h is 0.228nm, corresponding to the (111) crystal plane of Pd. 0.85 Co 0.15 TEM images of Figure 4 i) Spherical nanoparticles with smaller size were also observed, and the HRTEM images ( Figure 4 l) corresponds to the Pd (111) crystal plane. These characterization results are consistent with the previous XRD characterization. At the same time, combined with the analysis of energy dispersive X-ray spectroscopy (EDS), the local content distribution of elements in the sample was obtained (Table S1). The results show that the element content ratio is basically consistent with the feed ratio.
[0064] For different proportions of Pd x Co y Perform CV test. Figure 8 The CV graphs show that the catalysts with different ratios have excellent charge transfer kinetics. 0.5 Co 0.5 The large double layer capacitance indicates that Pd 0.5 Co 0.5 Large electrode surface area creates more catalytically active sites for efficient absorption and activation of NO3 - Although Pd has the largest dual capacitance, it is more prone to hydrogen evolution reaction. Figure 8 (ae) Pd with different ratios x Co y CV diagrams of the catalysts, Co and Pd 0.15 Co 0.85 , Pd 0.5 Co 0.5 , Pd 0.85 Co 0.15 , Pd; Figure 8 (f) Pd with different ratios x Co y of double layer capacitance.
[0065] Stability is another key parameter for evaluating the practical application of catalysts. Fig. 9 Stability testing, Fig. 9 a shows that the NH3 production and Faraday efficiency obtained after five cycles of testing have no obvious fluctuations, and have good cycle stability. More importantly, Pd 0.5 Co 0.5 It showed good long-term stability, and the current density did not decrease significantly after 48 hours of electrolysis (the electrolyte was replaced every 3 hours). Fig. 9 b) The results show that Pd 0.5 Co 0.5 The catalyst has high stability.
[0066] In this patent, Pd is designed x Co y Metal composite catalysts are used for electrocatalytic nitrate reduction. Pd doping transfers electrons from Pd atoms to Co, significantly improving the activity of electrocatalytic nitrate reduction. The effects of different ratios and catalyst loading on NRA performance were investigated. The results showed that when the ratio was Pd 0.5 Co 0.5 , with a loading of 0.4 mg cm -2 The best performance was obtained at -1.0 V vs. RHE. The NH3 production of its NRA was 1.72 ± 0.03 mg h -1 mg cat -1 , FE is 88.9±1.2%. When the initial concentration of nitrate is 100ppm, the NH3 selectivity is as high as 96.8±0.9%. In addition, after five cycle tests, it showed good stability and activity. At the same time, after a long-term test of 48h, its current density remained basically stable, with good durability.
[0067] The above embodiments and illustrations do not limit the product form and style of the present invention. Any appropriate changes and modifications made by ordinary technicians in the relevant technical field should be deemed to be within the patent scope of the present invention.
Claims
1. A palladium-cobalt nanosphere material for electrocatalytic synthesis of ammonia, characterized in that: The material morphology of the nano-microspheres is spherical; its chemical composition is characterized by Pd x Co y , x and y represent the molar fractions of Pd and Co respectively, x+y=1, and the ratio of x to y ranges from 15:85 to 50:50; and the diameter of the nanospheres is 100 to 300 nm.
2. The palladium-cobalt nanosphere material for electrocatalytic synthesis of ammonia according to claim 1, characterized in that: When the material is used as an electrocatalyst to catalyze the synthesis of ammonia, when the ratio of x to y is 1, that is, x=y=0.5, the loading amount is 0.4 mg cm -2 When Pd 0.5 Co 0.5 The catalyst has the highest NH3 yield of 1.72±0.03mg h at -1.0 V vs. RHE. -1 mg cat -1 and Faradaic efficiency 88.9±1.2%; when the initial concentration of nitrate is 100ppm, the NH3 selectivity is as high as 96.8±0.9%.
3. The palladium-cobalt nanosphere material for electrocatalytic synthesis of ammonia according to claim 2, characterized in that: At this time, the diameter of the nano-microspheres is about 300 nm and they are evenly distributed.
4. The palladium-cobalt nanosphere material for electrocatalytic synthesis of ammonia according to claim 2, characterized in that: After five cycle tests, it showed good stability and activity; after a long-term test of 48 hours, its current density remained basically stable, with good durability.
5. A method for synthesizing palladium-cobalt nano-microsphere materials for electrocatalytic synthesis of ammonia according to any one of claims 1 to 4, characterized in that: A quantitative amount of 19.2 mg to 101.1 mg PdCl2 and 146.5 mg to 26 mg CoCl2 was dissolved in 30 mL methanol solution. Under continuous stirring, 8 mL ZIF-67 suspension was transferred to the mixed solution. After being placed in a water bath at 50 to 70 °C for 2 h to 3 h, the mixture was washed three times with methanol. After drying overnight, the obtained powder sample was annealed at 360 °C for 2 h to 3 h in an Ar atmosphere to obtain Pd x Co y ; Pd was adjusted by changing the amount of PdCl2 and CoCl2 x Co y The molar fractions of Pd and Co in x Co y The x and y in the equation represent their respective mole fractions.
6. The use of a palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia according to any one of claims 1 to 4, characterized in that: Applied to electrocatalytic nitrate reduction to synthesize ammonia.
7. The use of a palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia as claimed in claim 6, characterized in that: The material is prepared into a working electrode for electrocatalytic reduction to synthesize ammonia, specifically in the following steps: Electrolyte configuration: The electrolyte concentration used is 100ppm NO3 - -N+0.1M Na2SO4 solution; Nafion 115 membrane treatment: The Nafion 115 membrane cut to the appropriate size was soaked in 80℃ 5wt% hydrogen peroxide for 1 hour, transferred to deionized water for 30 minutes, then treated in 80℃ 5wt% dilute sulfuric acid for 1 hour, and finally transferred to 80℃ deionized water for 30 minutes; Preparation of working electrode: Prepare the prepared Pd x Co y The catalyst was added to a mixed solution of ethanol and Nafion solution, wherein the volume ratio of ethanol to Nafion was 19:1; ultrasonic treatment was performed for 20 to 40 minutes to form a uniform suspension, and 200 μL of the suspension was evenly dropped on carbon paper (1.0 cm×1.0 cm), and vacuum dried for later use; Electrocatalytic NO3 - Reduction test: The electrochemical experiment was carried out in an H-type electrolytic cell separated by a Nafion 115 membrane, using a three-electrode system to load Pd x Co y The carbon paper of the catalyst was used as the working electrode, the platinum mesh electrode was used as the counter electrode, and the Ag / AgCl electrode (filled with saturated KCl solution) was used as the reference electrode to form a three-electrode system; the test environment was room temperature and atmospheric pressure; Before the test begins, Ar needs to be passed through the electrolyte for 20 minutes in advance to remove O2 in the electrolyte, and Ar should be kept flowing steadily in subsequent tests; the stirring rate during the test is 200-250rpm; the LSV test scan rate is 5mV / s, and it is carried out in the potential range of 0Vvs.RHE to -1.1Vvs.RHE; the constant potential test lasts for 1-1.5h at a potential of -1.1 to -0.7Vvs.RHE.
8. The use of palladium-cobalt nano-microsphere material for electrocatalytic synthesis of ammonia as claimed in claim 7, characterized in that: All potentials of the system are converted into reversible hydrogen electrode potentials by the following formula: E(vs.RHE)=E(vs.Ag / AgCl)+0.059pH+0.197.